Adsorption of 99mTc on aluminum oxide; Radiochemistry; Vol. 53, iss. 5 - Skuridin V. S. Viktor Sergeyevich; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Nesterov E. A. Evgeny Alexandrovich; Sadkin V. L. Vladimir Leonidovich; Rogov A. S. Alexander Sergeyevich (2011, 2011)
Title screen